The analysis of student satisfaction using academic services using services quality, IPA, and QFD methods - Velya Ramadhani; Firman (Universitas Negeri Padang, 2022)
This study aims to analyze student satisfaction with the academic services of the Department of Management, Faculty of Economics, Universitas Negeri Padang by using the Service Quality, Importance Performance Analysis (IPA), and Quality Function Deployment (QFD) methods. In this study, 216 students majoring in management in the class of 2018 and 2019 were selected using Simple Random Sampling. Data collection methods in this study were questionnaires and interviews. Based on the results of the calculation of the servqual score, it can be seen that the average gap shows a negative value of -0.29. This indicates that overall academic services can meet student expectations. Based on the results of the IPA analysis, there are 7 attributes that are in quadrant 1 which are the main priority in the improvement process. The seven attributes are continued in the QFD data processing which produces 11 technical responses that can be considered or input for the management department to improve academic services.